(Re)translations of the European Convention on Human Rights in Turkish - Kurmel, Deniz Kocak (SPRINGER-VERLAG SINGAPORE PTE LTD, 2019)
In the context of the European Convention on Human Rights, the act of translation has an important place. As the official languages of the Convention are English and French, it is mandatory to translate the Convention into the languages of the various state parties. The Convention in question was officially translated into Turkish in 1954 for the first time in the process of Turkey becoming a party to the Convention (Official Gazette, 19 March, 1954, no. 8662). In the following years, many non-official retranslations of the Convention have been carried out. The objective of this study is to examine the role the Turkish translation and retranslations of the Convention play in the implementation of the European Convention on Human Rights. This study explores the role of the official translation and retranslations of the Convention into Turkish (retranslations by Mehmet Semih Gemalmaz and Osman Dogru) with reference to the translation of the specific terms detention and arrest, which are the key terms of Article 5 of the Convention Right to liberty and security. This study analyzes the transfer of these terms into Turkish via the official translation and the retranslations by using a socioterminological (Gambier Y, Meta 32(3):314-320, 1987; Delavigne V, Meta 40(2):308-318, 1995; Gaudin F, Socioterminologie. Une approche sociolinguistique de la terminologie. Editions Duculot, Bruxelles, 2003) method, which deals with terms in their social context and examines their use within this specific discourse.
Keywords: Linguistics